Identifying and Assessing the Functionality of IT Systems for the Maintenance and Development of the Road Network - Marcin Świtała; Anna Ledwolorz (The Baltic Journal of Road and Bridge Engineering)
The article presents the results of research aimed at identifying and assessing the functionality of IT systems in activities related to the maintenance and development of the road network managed by local government units. Starting the research, the authors were operating under the assumption that, nowadays, IT systems should play an important role in solving problems related to the management of road infrastructure. The applied research method took a form of a survey, and the research sample consisted of 100 local government units acting as administrators of the road network, i.e., administrators of municipal roads (AMR), county roads (ACR) and operating within cities with independent county rights (ACCR). The results of the research indicate that few administrators utilise integrated information systems in practice. Their users turned out to be mainly representatives of the ACCR group, who use several different support systems on a daily basis, with different functionality and usability. The operation of IT systems is mainly used at the level of operational work related to the implementation of ongoing maintenance activities, excluding the possibility of using them in strategic management.